2018
DOI: 10.1016/j.cub.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Hippocampal CA1 and CA3 Differentially Mediate Learned Approach-Avoidance Conflict Processing

Abstract: Approach-avoidance conflict arises when an animal encounters a stimulus that is associated simultaneously with positive and negative valences [1]. The effective resolution of approach-avoidance conflict is critical for survival and is believed to go awry in a number of mental disorders, such as anxiety and addiction. An accumulation of evidence from both rodents and humans suggests that the ventral hippocampus (anterior in humans) plays a key role in approach-avoidance conflict processing [2-8], with one influ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 41 publications
7
75
1
Order By: Relevance
“…The hippocampus is a brain area involved in the perception of stressful contexts and the production of anxious behavior (Adhikari, Topiwala, & Gordon, 2010) and is implicated as a key brain area for devel oping new interventions to treat anxiety disorders (Gorman, 2003). All three major subregions of the hippocampus (i.e., the dentate gyrus (DG) and areas CA3 and CA1) form the trisynaptic circuit and each have been functionally implicated in moderating anxious behavior (Jimenez et al, 2018;Kheirbek et al, 2013;Schumacher et al, 2018). Interestingly, these areas are all highly plastic and undergo many structural changes in response to environmental stimuli.…”
Section: Structural Change In the Hippocampusmentioning
confidence: 99%
“…The hippocampus is a brain area involved in the perception of stressful contexts and the production of anxious behavior (Adhikari, Topiwala, & Gordon, 2010) and is implicated as a key brain area for devel oping new interventions to treat anxiety disorders (Gorman, 2003). All three major subregions of the hippocampus (i.e., the dentate gyrus (DG) and areas CA3 and CA1) form the trisynaptic circuit and each have been functionally implicated in moderating anxious behavior (Jimenez et al, 2018;Kheirbek et al, 2013;Schumacher et al, 2018). Interestingly, these areas are all highly plastic and undergo many structural changes in response to environmental stimuli.…”
Section: Structural Change In the Hippocampusmentioning
confidence: 99%
“…A currently popular notion of PFC suggests its key role in emotional processing and decision making (Damasio, 1996;Miller and Cohen, 2001) which often depends on weighing information about aversion and reward memories to control behavior. The PFC may exert its conflict resolution function through connections with other structures, such as the striatum (Berendse et al, 1992), thalamus (Choi et al, 2019), ventral hippocampus (Schumacher et al, 2018) and amygdala (McDonald et al, 1996;Gabbott et al, 2005), to name a few. A broad range of studies has shown that medial PFC (mPFC) encodes both rewarding (Otis et al, 2015) and aversive stimuli (Burgos-Robles et al, 2009).…”
Section: Interaction Of Competing Emotional Memories Circuitsmentioning
confidence: 99%
“…This involves considering the weights of each emotional memory because animals choose what behavior to execute guided by the relative weighs of opposing memories. Both early and recent works have made efforts to characterize approach-avoidance conflict (Miller, 1944;Choi and Kim, 2010;Friedman et al, 2015;Burgos-Robles et al, 2017;Schumacher et al, 2018;Choi et al, 2019;Verharen et al, 2019;Walters et al, 2019). We recently developed two related approach-avoidance conflict animal models that are set to separate discrete variables (reward memory retrieval, threat memory retrieval and their competition) in the same individual by putting variable weigh on reward-or threat-related memories through training, and therefore are amenable to study both sides of the coin: when reward has higher relative value than threat and vice versa.…”
Section: Using Conflict Choice Behavior To Understand Competing Emotimentioning
confidence: 99%
“…The hippocampus is a brain area involved in the perception of stressful contexts and the production of anxious behavior (Adhikari, Topiwala, & Gordon, 2010) and is implicated as a key brain area for devel oping new interventions to treat anxiety disorders (Gorman, 2003). All three major subregions of the hippocampus (i.e., the dentate gyrus (DG) and areas CA3 and CA1) form the trisynaptic circuit and each have been functionally implicated in moderating anxious behavior (Jimenez et al, 2018;Kheirbek et al, 2013;Schumacher et al, 2018). Interestingly, these areas are all highly plastic and undergo many structural changes in response to environmental stimuli.…”
Section: Structural Change In the Hippocampusmentioning
confidence: 99%